ISLAMIC CLASSROOM PASSWORDS TO INVIGORATE YOUNG LEARNERS’ ENTHUSIASM ON LEARNING ENGLISH - Triastama Wiraatmaja; Kharisma Naidi Warnanda Sabgini; Agista Nidya Wardani (PROJECT (Professional Journal of English Education), 2024)
Developing and composing Islamic Classroom passwords that is unique to the teaching and learning English deemed required for young learners. Therefore, this research emphasizes the significance of utilizing classroom passwords to pique young learners’ enthusiasm to learn English, especially Islamic-related classroom passwords. In addition, the Islamic Classroom Passwords were available in Bahasa and English. Afterwards, the community service team will assign the teachers to conduct the opening and closing lines of Islamic Classroom Passwords. Therefore, this kindergarten will possess distinctive qualities compared to other schools. The result showed that the classroom passwords were created and implemented to set the school's lessons apart from those of other schools. According to the plan, the students were engaged in the teachings since they were related to the classroom passwords. The teachers could also apply them. In conclusion, using Islamic Classroom Passwords can be a valuable tool for enhancing young learners' interest in learning English and helping them connect their faith with their language instruction. This approach can contribute to a more engaging and meaningful learning experience for students, promoting the integration of Islamic values in English language teaching.